PEMANFAATAN LAHAN BEKAS PENGGALIAN TANAH PEMBUATAN BATU BATA UNTUK PERSAWAHAN DI DESA GENTUNGANG KECAMATAN BAJENG BARAT KABUPATEN GOWA - Basir, Muhammad Ikbal (UNIVERSITAS NEGERI MAKASSAR, 2019)
ABSTRACTThis study aims to: to determine the physical properties of soil and the chemical properties of soil after extracting bricks to be made into rice fields. The variables used in this study are soil texture, Ph tanh, soil drainage class, effective soil depth, soil CEC, air temperature, rainfall and slope. Sampling in this study using Matching techniques. The results showed that the Gentungang Village can be divided into five (5) land units. Based on these land units, the land suitability for paddy fields is obtained according to the marginal class. Land suitability class for paddy fields in Gentungang Village especially in the sampling area is obtained by two land suitability classes namely S3-nr4 and S3-rc2nr4. Each land suitability class can be repaired according to the heaviest limiting factor, phosphate content, except soil texture cannot be done repair. Soil characteristics in the Gentungang Village are divided into two (2) namely physical and chemical properties. The physical properties include the drainage class is rather slow, the soil texture is moderate to slightly smooth, and the soil depth is> 50 cm. Meanwhile, chemical properties include CEC (> 16 and â‰¤ 16), pH H2O (6-7), Nitrogen content (low-medium) and Phosphate content (low-very low).